Dari Ruang Kuliah ke Lapangan: Pendekatan Interdisipliner Untuk Pengembangan Komunikasi Teknis Mahasiswa Teknik Sipil - Ambarwati, Atifa; Salsabila, Nalya; Siregar, Amirul Fadillah; Gulo, Joel Alfian S; Ginting, Wahyu Prayoga; Pulungan, Hendra Kurnia (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Technical communication skills are an essential competency for civil engineering students, not only in academic contexts but also in professional practice in the field. This article aims to explore an interdisciplinary approach in developing technical communication skills of civil engineering students by emphasizing the connection between the classroom and the workplace. Through a literature review and critical analysis of various learning models such as project-based learning, cross-disciplinary collaborative approaches, and information technology integration, this study highlights effective strategies that can improve technical report writing, professional presentation, and collaborative communication skills in multidisciplinary teams. The results of the discussion indicate that the application of an interdisciplinary approach can narrow the gap between theory and practice, while strengthening students' readiness to face communication challenges in the complex world of construction. Thus, this article provides conceptual and practical contributions in designing a relevant and applicable technical communication learning model for civil engineering education in the modern era